On the concept of "architectural science" - Tarasova Irina V. (Архитектон)
The article examines the variety of interpretations of the concept of "architectural science" presented in scientific publications. A review of interpretations of the concept of architectural science by different researchers is instrumental at an initial stage when considering architectural science as a special phenomenon. The evolvement of ideas related to the concept of "architectural science" is demonstrated along with the diversity of formulations proposed by different researchers. The author proposes her concept of "architectural science" that would allow considering architectural science as an independent sphere in various modern knowledge classification systems.